Disain Dan Fabrikasi Mesin Sputtering Skala Laboratorium untuk Penumbuhan Film Tipis - Muhammad, Bagja Restu; Nugroho, Aris Widyo (Semesta Teknika, 2017)
Plasma sputtering is well known method for preparation of thin films on various substrates. This technique involves expelling material from a target onto substrate in a vacuum chamber. Generally, the technique is equipped with argon supply system for ionized gas bombardments of the target. This work shows designing and fabricating process of a simple sputtering machine without gas supply system and its preliminary thin film preparation test. A CAD software was applied to design its main apparatus namely a vacuum system and an electrical system. Afterward, those apparatus were fabricated and assembled. Preliminary test was conducted using a cooper plate as a target and plate glasses as substrates for 90 s and 130 s processing time. The vacuum pressure, voltage and the electric current were set up at 10-2 torr, 150 volt and 1 A, respectively. The thin film on the glass was visually examined andÂ  its resistivity was measured using ohm meter. The results show that a cooper thin film has been coated on the glass with the resistivity of 12.6 and 9 â¦. At this stage , it is confirmed that the plasma sputtering machine being fabricated has successfully worked.